Iron precipitation in a natural CO2 reservoir: Jurassic Navajo Sandstone in the northern San Rafael Swell, UT, USA. Issue 1 (11th January 2013) - Potter‐McIntyre, S.; Allen, J.; Lee, S.‐Y.; Han, W. S.; Chan, M.; McPherson, B.
Abstract Diagenetic iron (oxyhydr)oxide minerals are common precipitates expected in CO2 reservoirs, and these minerals record fluid flow for application to carbon capture and sequestration (CSS). Multiple mineralogy and spectroscopy analyses on a pore to meter scale characterize a well‐exposed, lithologically controlled, iron (oxyhydr)oxides reaction front in the Jurassic Navajo Sandstone. Dolomite is the most prevalent cement (up to 23 area%), followed by only several percent or less of iron (oxyhydr)oxides, kaolinite, illite, and gypsum cements. Bulk geochemistry based on diagenetic mineralogies in the reaction front is compared with the water chemistry from nearby modern spring effluent emanating from the Navajo Sandstone to conclude that similar fluids (i.e., CO2‐charged, saline waters containing hydrocarbons) are responsible for the precipitation. A second comparison of bulk geochemistry and diagenetic mineralogies of the reaction front with data from other abundant Navajo Sandstone concretions in the Spencer Flat region (in south central Utah) shows that reservoir fluids likely vary spatially and temporally in the porous and permeable Navajo Sandstone. CO2 injection into porous and permeable, quartz arenite, saline aquifers will likely result in minor clay and abundant dolomite precipitation that will significantly decrease porosity.